CHARACTERS IN THE ARABIC NOVEL AND THEIR DESTINIES NAJEEB MAHFOUZ'S NOVELS AS A MODEL (American Journal of Research in Humanities and Social Sciences, 2024)
This study dealt with the description and analysis of characters in the Arabic novel, as the character occupies an important position in the novel, as it is a tool and means for the novelist to express his vision and ideas, and is considered one of the most prominent and important elements in the novel structure, as it is the artistic image that carries the realistic connotations and contents that the writer links in the novel work, and the novelist or writer often borrows his characters from the reality that society lives in or mixes with them some features from the imagination to be more influential and convincing, and this is one of the secrets of the success of the writer who is creative in creating the complete novel character. This study consisted of an introduction, a preliminary entrance, and a definition of character in language and terminology, then the levels of description of the fictional character and its function, and the types of character in the novel, and then an analysis of the characters in Naguib Mahfouz's novels, which are: (Miramar Novel, Al-Harafish Novel, Afrah Al-Qobba Novel, New Cairo Novel, Chatter on the Nile Novel, The Thief and the Dogs Novel).